NK92 Expressing Anti-BCMA CAR and Secreted TRAIL for the Treatment of Multiple Myeloma: Preliminary In Vitro Assessment - Motais, Benjamin; Charvátová, Sandra; Walek, Zuzana; Hájek, Roman; Bagó, Juli R (Cells, 2023)
Multiple myeloma (MM) has witnessed improved patient outcomes through advancements in therapeutic approaches. Notably, allogeneic stem cell transplantation, proteasome inhibitors, immunomodulatory drugs, and monoclonal antibodies have contributed to enhanced quality of life. Recently, a promising avenue has emerged with chimeric antigen receptor (CAR) T cells targeting B-cell maturation antigen (BCMA), expressed widely on MM cells. To mitigate risks associated with allogenic T cells, we investigated the potential of BCMA CAR expression in natural killer cells (NKs), known for potent cytotoxicity and minimal side effects. Using the NK-92 cell line, we co-expressed BCMA CAR and soluble tumor necrosis factor-related apoptosis-inducing ligand (sTRAIL) employing the piggyBac transposon system. Engineered NK cells (CAR-NK-92-TRAIL) demonstrated robust cytotoxicity against a panel of MM cell lines and primary patient samples, outperforming unmodified NK-92 cells with a mean difference in viability of 45.1% (±26.1%, depending on the target cell line). Combination therapy was explored with the proteasome inhibitor bortezomib (BZ) and γ-secretase inhibitors (GSIs), leading to a significant synergistic effect in combination with CAR-NK-92-TRAIL cells. This synergy was evident in cytotoxicity assays where a notable decrease in MM cell viability was observed in combinatorial therapy compared to single treatment. In summary, our study demonstrates the therapeutic potential of the CAR-NK-92-TRAIL cells for the treatment of MM. The synergistic impact of combining these engineered NK cells with BZ and GSI supports further development of allogeneic CAR-based products for effective MM therapy.
Keywords: Immunotherapy, Adoptive; imunoterapie adoptivní; lidé; chimerické antigenní receptory; B-Cell Maturation Antigen; Bortezomib; Multiple Myeloma; Receptors, Chimeric Antigen; Humans; Quality of Life; mnohočetný myelom; bortezomib; maturační antigen B-buněk; kvalita života